2002
DOI: 10.1021/jp015508i
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and Predissociation of Acetylene in the np Gerade Rydberg States

Abstract: The np gerade Rydberg states of acetylene were studied with various spectroscopic techniques to measure one-color resonant multiphoton ionization (REMPI) spectra, two-color REMPI mass spectra, fluorescence spectra, and fluorescence excitation spectra in the two-photon energy region of 72 000-92 000 cm -1 . The rotational analysis was successfully performed for one of the upper levels, which was assigned to the 4p 1 ∆ g Rydberg state. All of the gerade Rydberg states prepared under the two-photon resonance cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…This conclusion is in accordance with our previous assignments. 21 The quantum defects calculated for the Rydberg states of C 2 D 2 are almost the same as those for C 2 H 2 and roughly classified into three values; 0.5, 0.6, and 1.1 corresponding to npπ 1 Σ g + , npπ 1 Δ g , and npσ 1 Π g , respectively. Considering quantum defects, vibrational frequencies, and band intensities, we assigned the diffuse bands to transition to the npπ gerade Rydberg states of C 2 D 2 and C 2 H 2 as listed in Table 2.…”
Section: ■ Experimental Sectionmentioning
confidence: 64%
See 4 more Smart Citations
“…This conclusion is in accordance with our previous assignments. 21 The quantum defects calculated for the Rydberg states of C 2 D 2 are almost the same as those for C 2 H 2 and roughly classified into three values; 0.5, 0.6, and 1.1 corresponding to npπ 1 Σ g + , npπ 1 Δ g , and npσ 1 Π g , respectively. Considering quantum defects, vibrational frequencies, and band intensities, we assigned the diffuse bands to transition to the npπ gerade Rydberg states of C 2 D 2 and C 2 H 2 as listed in Table 2.…”
Section: ■ Experimental Sectionmentioning
confidence: 64%
“…20 In our previous study, we found the 4pπ 1 Δ g and 4pπ 1 Σ g + states of acetylene using one-color (2 + 1) REMPI spectroscopy. 21 We found that the lifetime of the 0°level in the 4pπ 1 Δ g state was sufficiently long to record the rotationally resolved spectrum. We also found that the photofragment C 2 emission of Swan bands (C 2 d 3 Π g −a 3 Π u ) was induced by the multiphoton absorption via the two-photon resonance gerade Rydberg states of C 2 H 2 , and we succeeded in recording a wider energy range of the C 2 H 2 excitation spectrum.…”
Section: ■ Introductionmentioning
confidence: 78%
See 3 more Smart Citations